Heavy metal removal by oil palm empty fruit bunches (OPEFB) biosorbent - Daneshfozoun, S. (Trans Tech Publications Ltd, 2014)
This study developed an effective and economical physical pretreatment of OPEFB to be used as biosorbent for the removal of heavy metal ions such as Cu+2, Zn+2 and Pb2+. The effects of fibres sizes, metal ions concentration (100-1000 ppm), initial pH (4-10) and contact time (20-150 min) were investigated in batch system. Samples were characterized with Atomic Absorption Spectrometry (AAS), Transmission Electron Microscopy (TEM) and Fourier Transmission Infra-red Spectroscopy (FTIR). Results showed pH-dependence adsorption efficiency and increased adsorption with initial metal concentrations where more than 92 adsorption efficiency achieved. We have successfully developed an eco-friendly, low cost adsorbent without any chemical modification or excessive energy disposal. Â© 2014 Trans Tech Publications, Switzerland.